2001
DOI: 10.22358/jafs/68004/2001
|View full text |Cite
|
Sign up to set email alerts
|

Tannin content affects negatively nutritive value of pea for monogastrics

Abstract: Nine Polish varieties of pea (P. sativum L.) differing in flower colour, from white to purple, were evaluated for chemical and amino acid composition and in vitro for predicted ileal digestibility of protein (pdN) and predicted digestibility of energy (pdE) for pigs. In selected varieties differing in tannin content the apparent metabolizable energy value corrected for zero N balance (AME N ), apparent digestibility of protein and fat and effect of enzymes reducing viscosity of digesta on this parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
76
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 16 publications
15
76
0
4
Order By: Relevance
“…Similarly, the in vitro predicted SID values decreased linearly (P , 0.05) as the contents of condensed tannins in the faba bean cultivars increased (r 2 5 0.77 for His to r 2 5 0.80 for Met and Thr) ( Table 5). In agreement with this observation, Smulikowska et al (2001) reported a detrimental effect of increasing levels of condensed tannins on CP digestibility in field peas under in vitro conditions. Condensed tannins are known to exert negative effects on protein digestibility, such as they may form complexes with both dietary proteins and digestive enzymes (Jansman, 1993), which in turn may inhibit the activity of proteolytic enzymes and/or increase the secretion of endogenous proteins (Marquardt, 1989).…”
Section: Resultssupporting
confidence: 81%
“…Similarly, the in vitro predicted SID values decreased linearly (P , 0.05) as the contents of condensed tannins in the faba bean cultivars increased (r 2 5 0.77 for His to r 2 5 0.80 for Met and Thr) ( Table 5). In agreement with this observation, Smulikowska et al (2001) reported a detrimental effect of increasing levels of condensed tannins on CP digestibility in field peas under in vitro conditions. Condensed tannins are known to exert negative effects on protein digestibility, such as they may form complexes with both dietary proteins and digestive enzymes (Jansman, 1993), which in turn may inhibit the activity of proteolytic enzymes and/or increase the secretion of endogenous proteins (Marquardt, 1989).…”
Section: Resultssupporting
confidence: 81%
“…Good production performance of birds in all treatments and consistent feed intake suggest that the pea cultivar studied did not appear to contain harmful levels of ANF. This confirms the results by Smulikowska et al (2001), who reported that the role of ANF in modern pea cultivars is found to be less important. However growth and FCR depressing effects of peas might be alleviated through provision of DL-methionine and L-lysine, as shown previously by Igbasan and Guenter (1996).…”
Section: Effect Of Pea Inclusionsupporting
confidence: 92%
“…Furthermore, the result showed that the effects of TA depended on the temperature condition. In high temperature condition, Ebrahim et al Smulikowska et al, 2001). The biological effect of tannins in poultry nutrition is related to their adverse effects on feed intake (Armstrong et al, 1974) and nutrient utilization (Smulikowska et al, 2001).…”
Section: Growth Performancementioning
confidence: 99%
“…In high temperature condition, Ebrahim et al Smulikowska et al, 2001). The biological effect of tannins in poultry nutrition is related to their adverse effects on feed intake (Armstrong et al, 1974) and nutrient utilization (Smulikowska et al, 2001). Armstrong et al (1974) showed that addition of tannic acids with varying molecular weights to a non-resistant sorghum grain diet resulted in significant depressions in chicken performance.…”
Section: Growth Performancementioning
confidence: 99%
See 1 more Smart Citation